"What is Human, Only what is Human ... " The Problem of Suffering in Leonid Leonov’s Novel "The Pyramid" - Listwan, Fryderyk (Respectus Philologicus, 2006)
The article considers the hitherto unresearched problem of suffering in Leonid Leonov’s last novel, "The Pyramid". Numerous linguistic (lexical, phraseological and syntactic) markers of this problem have been found in Leonov’s novel: synonym of the noun "suffering", intertextual elements referring to the Bible and antique mythology, proverbs, aphorism, which belong to the semantic field of the base word "suffering". The article also presents the point of view of the characters in relation to the causes of suffering and its role in human life; besides, the attitude to spiritual torment is discussed. Based on the characters’ statements and the logic of events, three main causes of suffering are distinguished: the eternal struggle between God and Satan to win man, an attempt to realise the idea of earthly paradise without Christ, and love for Russia. Among the characters’ attitudes to suffering, first of all, submissiveness is distinguished, which leads to the reconciliation with cruel reality and to the justification of both God (theodicy of the priest Matvey Loskutov) and the man (anthropodicy of Stalin and his ardent supporter Vadim Loskutov). The characters seek the sources of the submission to Stalinist terror in the Gospel, which has determined some features of the Russian character (Matvey), either in the Gospel or in the desire to realise the immemorial dream of the "golden age", which is encoded in human awareness (Vadim).